Implementation of Basel II and Good Corporate Governance towards Risk Managementin Indonesian Banking Industry - Andriani Hapsari, Ajeng; Bayu Aji Sumantri, Muhammad; Haizam Mohd Saudi, Mohd; henry, John (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to examine the effect of Basel Capital Accord and Good Corporate Governance regulations on risk management in Indonesian banking. The Basel Capital Accord variable is obtained from the report of the Directorate of Banking Research and Regulation of Bank Indonesia on Basel II Implementation in Indonesia, and the GCG variable is measured using the self-assessment method according to Bank Indonesia Circular Letter No. 9/12/DPNP. The population of this study is all Indonesian banks listed on the Indonesia Stock Exchange during the period 2011 to 2016 with the method of panel data regression analysis. This research is descriptive verification research with the purposeful sampling method, which is one of the non-probability sampling methods. From the results of the study, it was found that the minimum capital ratio and operational risk positively and significantly influence the management of credit risk banking. While Ratio of Capital Adequacy Ratio and Operational Risk have a positive and significant impact on operational risk management. Credit Risk has a negative and significant effect on credit risk management as well as the Adequacy adequacy ratio, which negatively and significantly influences operational risk management